Stress corrosion crack initiation testing with tapered specimens in high-temperature water – results of a collaborative research project - Yuchen Gu (Corrosion Engineering, Science and Technology, 2021)
The applicability of an accelerated test technique using tapered tensile specimens for investigating thestress corrosion crack (SCC) initiation behaviour of structural materials in high-temperature water wasassessed in the framework of a European collaborative research project (MICRIN – MItigation of CRackINitiation). The main advantage of using a tapered geometry is, that in a single test a stress gradient isobtained through the gauge length, and therefore a stress threshold for SCC initiation can bedetermined in a reasonable timeframe. This method was used to investigate two different materialsthat were known to be susceptible to SCC in light water reactor environment: a high-Si stainlesssteel and a Ni-base weld metal (Alloy 182). The results of the international test programmeconfirmed that the tapered specimen test methodology could be used to identify a SCC initiation stress threshold, albeit that significant scatter was present in the data.